BAYMEC lobbies school board. - Sahl, Ted (photographer):::Creator::::::::::::
BAYMEC, a gay and lesbian political pac lobbies the San Jose Unified School District on behalf of gay rights. Photograph shows Wiggsy Sivertsen at the podium.